Beyond limits :|the mobilization of a wildcat strike in Turkey - Gökçek, Alican Çağrı. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
With the increasing poverty and rising social injustice in Turkey, the working class’ grievances have recently become more visible in the public. In this sense, Turkish society witnessed one of the most disruptive and crowded labor strikes during the neoliberal capitalist era in 2015. During these strikes, metal workers mainly targeted the hegemonic partnership of employers and pro-employer trade union, Turkish Metal Union (TM). Both the rising poverty in the social and economic conditions of workers and the untenable forms of practices by the hegemonic partners led workers to rely on their own power and go on a wildcat strike. In this paper, I tried to search for possible answers to two basic questions about this strike wave. First, the nature of crisis which precipitated this mass action and the nature of these strikes were important issues to identify. Second, the influence of the metal workers’ movement led me to think about what this contentious action might bring to social movement theories. For reaching these research intentions, I followed a qualitative method and heavily relied on semi-structured interviews conducted with defiant workers. In addition to those interviews, I also used media news, statistical data, and elite interviews with union officers, union representatives, and labor activists. Essentially, this research should be considered more than a case study to the extent that it tries to look at what the strike wave tell us for developing a more reliable and replicable social movement theory for the future studies.
Keywords: Metal-workers -- Labor unions -- Turkey.; Strikes and lockouts -- Turkey.